Pharmacological Treatments Inhibiting Levodopa-Induced Dyskinesias in MPTP-Lesioned Monkeys: Brain Glutamate Biochemical Correlates - Morin, Nicolas; Di Paolo, Thérèse (Frontiers in Neurology, 2014)
Antiglutamatergic drugs can relieve Parkinson’s disease (PD) symptoms and decrease L-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesias (LID). This review reports relevant studies investigating glutamate receptor subtypes in relation to motor complications in PD patients and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned monkeys. Antagonists of the ionotropic glutamate receptors, such as NMDA and AMPA receptors, display antidyskinetic activity in PD patients and animal models such as the MPTP monkey. Metabotropic glutamate 5 (mGlu5) receptor antagonists were shown to reduce the severity of LID in PD patients as well as in already dyskinetic non-human primates and to prevent the development of LID in de novo treatments in non-human primates. An increase in striatal post-synaptic NMDA, AMPA and mGlu5 receptors is documented in PD patients and MPTP monkeys with LID. This increase can be prevented in MPTP monkeys with the addition of a specific glutamate receptor antagonist to the L-DOPA treatment and also with drugs of various pharmacological specificities suggesting multiple receptor interactions. This is yet to be well documented for presynaptic mGlu4 and mGlu2/3 and offers additional new promising avenues.